The association of hamstring tightness with lumbar lordosis and trunk flexibility in healthy individuals: gender analysis - Allam, Nesma M.; Ebrahim, Hasnaa Ali; Megahed Ibrahim, Ateya; Elneblawi, Nora Helmi; El-Sherbiny, Mohamed; Fouda, Khaled Zaki (Frontiers in Bioengineering and Biotechnology, 2023)
The purpose of this study was to investigate if there is a relation between hamstring tightness and lumbar lordosis as well as trunk flexibility based on gender differences and to analyze the differences in hamstring tightness, lumber lordosis and trunk flexibility in healthy adults.Methods: One hundred young healthy adults were recruited and distributed into 2 equal groups according to gender: group A (female group) and group B (male group). Hamstring tightness (HT) was measured by Active Knee Extension (AKE) test and Straight Leg Raise (SLR) test, the angle of lumbar lordosis was measured with a flexible ruler from standing position and trunk flexion flexibility (TFF) was measured by Fingertip-to-Floor Test.Results: There was a significant correlation between TFF and both measures of HT (SLR, p = 0.001; AKE, p = 0.001) in females. While, there was a non-significant correlation in males (SLR, p = 0.900; AKE, p = 0.717). Moreover, there was a non-significant correlation between lumbar lordosis and HT measures in both groups as (p > 0.05). Furthermore, there were significant differences between males and females in hamstring flexibility, TFF and lumbar lordosis as (p < 0.05).Gender differences in the relationship between hamstring tightness and trunk flexion flexibility are significant. However, there was no significant difference between males and females in the relationship between hamstring tightness and lumbar lordosis.